Harnessing platelets as functional vectors for contrast enhanced ultrasound imaging and fluorescence imaging. Issue 72 (18th December 2019) - Gao, Chuang; Bhattarai, Pravin; Zhou, Yiming; Zhang, Nisi; Hameed, Sadaf; Yue, Xiuli; Zhao, Bo
Abstract : The recent progress in the development of highly biocompatible nanoplatforms mostly encompasses the use of biological excipients such as red blood cells, cancer cell membranes, and also platelets. Abstract : The recent progress in the development of highly biocompatible nanoplatforms mostly encompasses the use of biological excipients such as red blood cells, cancer cell membranes, and also platelets. Such specialized vectors, if mimicked correctly, have intrinsic ability to navigate through the biological system and perform their intended action without eliciting any cascade of inflammatory processes. Naturally, platelets have been found to accumulate in the wound sites and also interact with circulating tumor cells (CTCs). Inspired by the targeting ability of platelets and the clinical success of ultrasound, herein we developed a novel ultrasound contrast agent (UCA) by backfilling of an insoluble gas into the platelets after lyophilization ex vivo . The as-prepared platelet-based ultrasound contrast agent (P-UCA) disguised the structural integrity of the natural platelets with an average diameter of 3.1 ± 0.4 μm, and could enhance the ultrasound signal both in vitro and in vivo . Besides, we further evaluated that such platelet particles could facilitate active loading of ICG molecules for prolonged in vivo fluorescence imaging compared to the free ICG. Taking all the results together, we established that biological structures such as platelets could be repurposed ex vivo as a"shell" to encapsulate gas and be further extended to load ICG for real-time ultrasound and fluorescence imaging respectively. This not only indicates many potential uses of these MBs in the diagnosis of platelet-related diseases, such as vascular damage, thrombosis, and atherosclerosis, but also serves as a powerful platform with multimodal theranostic capability after active loading of a variety of therapeutic and diagnostic agents.